Analisis Kasus Pembunuhan Istri di Kota Cilegon: Studi kasus putusan 871/Pid.B/2024/PN SRG - Nabilah Puteri Kurnia; Sinta Dewi Murni; Rifan Luqman Hakim; Muhamad Ari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Domestic homicide cases, especially those resulting from Domestic Violence (DV), are a phenomenon that has a wide impact, both on the surrounding environment and on the fulfillment of victims' rights. This study aims to analyze how the community responds to domestic violence murder cases and to identify victims' rights that are not fulfilled based on applicable legal regulations. Using empirical legal research methods, this study collected data through interviews with the Head of RT Jokolukito and reviewed relevant regulations. The results of the study indicate that the surrounding environment tends to be less concerned about domestic violence cases until they reach a fatal stage, which can be explained through Strain Theory and Cycle of Violence. In addition, it was found that victims did not receive optimal legal protection before the incident, and their rights after the incident were not fulfilled in accordance with the Domestic Violence Law and the Witness and Victim Protection Law. Therefore, this study recommends increasing public awareness, facilitating access to legal assistance for victims, and implementing a more effective restitution mechanism to ensure justice for victims and their families.